How Do the Young People Picture Out Their Use, Activeness, and Connectivity on Social Media? A Discourse Analysis Approach - Rahmat, Wahyudi; Tiawati, Refa Lina; Kemal, Edwar; Tatalia, Ricci Gemarni; Azri, Harizqi; Wulandari, Yosi (The Journal of communication inquiry, 2023)
In the past few years, young people have been using social media platforms to inform, share, and deliver their feelings. However, social media platforms like Facebook lost popularity among the young generations. Now, they prefer to interact via social media sites, such as Instagram, as narrative-based features. This study explores how young people use social media to their daily concerns. This article employs an anthropological methodology and discourse analysis to investigate the social media discourses among Padang's young people. As the capital of West Sumatra, Indonesia, Padang city provides a warm and welcoming environment for the young generation, making it an ideal place to grow spiritually and socially. Therefore, these young people's participation in the platforms are influenced by the issues reflecting their daily life. Nevertheless, it is considered that some of their behaviors can be explained by the trend of increased social media usage among their citizens.